1990
DOI: 10.1246/bcsj.63.364
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Magnetic and Spectroscopic Characterization of Novel Di-μ-carboxylato-Bridged Binuclear Copper(II) Complexes with 1,10-Phenanthroline

Abstract: Bis(μ-carboxylato-O,O′)-diaquabis(1,10-phenanthroline)dicopper(II) dinitrate tetrahydrates, [Cu(RCOO)(phen)(H2O)]2(NO3)2·4H2O, where R=H, CH3, and (CH3)3C, were prepared and characterized by elemental analyses, electronic spectra, magnetic susceptibilities, and X-ray structure analysis. The magnetic susceptibility data conform to the usual dimer equation. The −2J values are 125 cm−1 for formate, 86 cm−1 for acetate, and 99 cm−1 for 2,2-dimethylpropanoate. The crystal structures of [Cu(HCOO)(phen)(H2O)]2(NO3)2·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
41
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 13 publications
11
41
0
Order By: Relevance
“…This motif is rare amongst the various binding motifs that have been reported in the literature for copper(II)-acetato complexes (see Figure 2). Tokii et al [30] reported the same binding mode in a copper(II) complexes with 1,10-phenanthroline ligands. Their reported Cu···Cu separation of 3.063(3) Å is much shorter than that found in C m due to the π-π interaction between the chelating phen ligands on the two copper centres forming the dinuclear complex.…”
Section: Crystallographymentioning
confidence: 69%
“…This motif is rare amongst the various binding motifs that have been reported in the literature for copper(II)-acetato complexes (see Figure 2). Tokii et al [30] reported the same binding mode in a copper(II) complexes with 1,10-phenanthroline ligands. Their reported Cu···Cu separation of 3.063(3) Å is much shorter than that found in C m due to the π-π interaction between the chelating phen ligands on the two copper centres forming the dinuclear complex.…”
Section: Crystallographymentioning
confidence: 69%
“…[15,102,104] To consider the effect of this structural feature on the coupling constant we have displaced the four water molecules that replace two carboxylato bridges (7) by increasing the O b -Cu-O t angle to 1808 and moving the axial…”
Section: Computational Methodologymentioning
confidence: 99%
“…[15,102,104] Replacement of the four water molecules by ammonia decreases the strength of the antiferromagnetic coupling. For acetato-bridged compounds the coupling constant is reduced by 20 cm À1 , from À 179 to À 159 cm À1 .…”
Section: Computational Methodologymentioning
confidence: 99%
“…Experimental data were used as the starting point in the global optimizations of [SiW 12 3 + (C 1 , S = 3 = 2 ) cationic complexes. For the cationic complexes, the standard 6-31G(d) [31] basis has been chosen for all atoms.…”
Section: Synthesis Ofmentioning
confidence: 99%
“…[12] It comprises two squarepyramidal Cu atoms bridged by two acetate anions in a synsyn fashion with a CuÀCu length of 3.06 . Each basal plane is formed by two phenanthroline N atoms and two acetate O atoms, the apical position being occupied by a water molecule (Figure 3a).…”
Section: Introductionmentioning
confidence: 99%